2007
DOI: 10.1093/humrep/dem225
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing twins: a predictor of small-for-gestational age in IVF singletons

Abstract: IVF singletons with a vanished co-twin had a higher rate of SGA than singletons from a single gestation and the risk of SGA is increased with increasing gestational age at the time of vanishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 30 publications
8
84
1
6
Order By: Relevance
“…Second, adverse medical events before 20 weeks of gestation (spontaneous one-twin demise or termination) are likely more common among older mothers and may result in a shift of riskier pregnancies from twin to singleton. The surviving twin is at elevated risk of mortality, low birth weight, preterm birth and NICU admissions, 25,26 and contributes to the higher risk of adverse birth outcomes among singletons as opposed to twins.…”
Section: Discussionmentioning
confidence: 99%
“…Second, adverse medical events before 20 weeks of gestation (spontaneous one-twin demise or termination) are likely more common among older mothers and may result in a shift of riskier pregnancies from twin to singleton. The surviving twin is at elevated risk of mortality, low birth weight, preterm birth and NICU admissions, 25,26 and contributes to the higher risk of adverse birth outcomes among singletons as opposed to twins.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of diagnosis of VT has increased as twin pregnancies have risen in number following the use of ART and as the diagnostic tool, namely the transvaginal ultrasound, has been improved. The prevalence of VT has been reported at 4%-30% after ART, and the impact on obstetric and neonatal outcome has been discussed [1][2][3][4][5][6][7]. Almog et al [1] compared 57 VT deliveries with 171 matched singleton deliveries after ART and observed lower birth weight, an increased rate of low birth weight <2500 g and an increased rate of delivery at <28 weeks of gestation in the VT group.…”
Section: Discussionmentioning
confidence: 99%
“…Pinborg et al [3,4] conducted a retrospective study, including the cases of VT into the third trimester, and showed higher rates of low birth weight, very low birth weight, preterm delivery, and infant mortality associated with VT. They also showed that these risks were almost entirely because of the demise at >8 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations